Mathematical Modeling of Drinking Water Losses Management Case Study – Cairo - Egypt (International Journal of Scientific Research and Management (IJSRM), 2024)
Water, As A Precious natural resource, necessitates sustainable management to minimize wastage. Excessive leakage, particularly in regions confronting water scarcity such as Egypt, directly undermines environmental objectives and principles of cost recovery. Effective water management is pivotal for reducing losses and optimizing efficiency. Accurate measurement of water production and distribution is essential to identify losses and assess water utilities’ performance. This data aids in pinpointing the root causes of losses, whether physical or commercial, facilitating targeted reduction strategies. Forecasting supply-demand balance is critical for planning water networks and treatment facilities. Detailed infrastructure information enables decision-makers to discern areas experiencing water shortages and those with surplus resources. Our aim is to probe the causes of water losses in Cairo’s drinking water network, the capital of Egypt, and propose managerial solutions. Operational efficiency relies on minimizing labor, material, and energy costs. Water loss poses a significant operational challenge, as components of non-revenue water can significantly impact utilities’ financial stability. The IWA Water Balance offers a standardized approach to water audits, facilitating a comprehensive analysis of water production, storage, and distribution. This analysis aids in quantifying the magnitude of the water loss problem and prioritizing corrective actions based on revenue and non-revenue water components. The Cairo Water Company is entrusted with producing 5.5 million cubic meters of purified drinking water per day from 11 treatment plants, serving a network spanning 13,307 kilometers and supported by 20 maintenance centers. With a focus on serving 1.1 million citizens in compliance with Egyptian regulations, our study encompasses various metrics, including billed and unbilled consumption, unauthorized usage, and metering inaccuracies, to calculate commercial losses. Additionally, we evaluate main and storage leakages, as well as service connection leakages up to the customer meter, to determine technical losses. Through a mathematical module, we compute non-revenue water (NRW) and infrastructure leakage index (ILI) metrics. Performance indicators are utilized to assess the effectiveness of water utilities in managing losses and asset maintenance. Our designed module empowers decision-makers to evaluate and enhance asset methodologies for water loss management.